Intelligent and adaptive tutoring through a social network for higher education. Issue 3 (1st October 2020) - Troussas, Christos; Krouska, Akrivi; Alepis, Efthimios; Virvou, Maria
ABSTRACT: Social Media have become a tool for communication among people, the majority of whom belong to the younger generation. Hence, exploiting them in the educational field can promote communication and collaboration among students and instructors. Moreover, expanding them with more pedagogical tools, such as assessments and adaptivity, can improve further the learning outcomes. In view of the above, this paper presents i-LearnC#, an intelligent tutoring application over Facebook, for learning programming. This Facebook app extends the capabilities of Facebook platform to be used as an integrated tutoring system. In particular, i-LearnC# embodies an intelligent Virtual Coach offering individualised advice, covering students' knowledge gaps and solving queries on unknown learning concepts. Regarding students' assessment, i-LearnC# applies the Revised Bloom Taxonomy and delivers personalised assistance to them through the Virtual Coach. Finally, i-LearnC# employs cluster analysis for recommending the optimal groups for collaboration to students. i-LearnC# was evaluated using a well-known framework, the statistical hypothesis test and system's log files. The results are very promising, showing that i-LearnC# has been educationally beneficial to students in higher education promoting effective learning and teaching of computing education and achieving high acceptance rate as an adaptive intelligent social learning environment.